IMPLEMENTASI HAK DAN KEWAJIBAN PEMBERI BANTUAN HUKUM KEPADA PENERIMA BANTUAN HUKUM DALAM PERSPEKTIF HUKUM ISLAM DI PROVINSI BANTEN - Kurniawan, Dede (An Nawawi, 2024)
Law No. 16 of 2011 concerning Legal Aid aims to ensure access to justice for the poor through the provision of free legal aid. This study analyzes the application of regulations and identifies their inhibiting factors. This research seeks to find solutions to improve the performance of legal aid providers and access to justice for the poor and vulnerable. This study uses a qualitative method with a normative juridical approach. Secondary data consists of primary legal materials (laws and regulations), secondary legal materials (books and journals), and tertiary legal materials (internet). The data collection technique is through reading, observing, and analyzing literature materials, with narrative analysis as an analysis method. The findings of the study revealed that the implementation of Law No. 16 of 2011 in Banten Province was regulated through Regional Regulation No. 3 of 2014 and involved 21 accredited Legal Aid Institutions. Despite clear regulations, implementation faces challenges such as limited funding and a complicated accreditation process. To increase effectiveness, improvements are needed in funding and simplification of accreditation procedures. This ensures optimal and sustainable services for the poor